Hunting cetaceans with sound: a worldwide review - Brownell Jr. , Robert L.; Nowacek , Douglas P.; Ralls , Katherine (J. Cetacean Res. Manage., 2023)
Cetaceans are sensitive to a variety of anthropogenic sounds because they normally use sound to navigate, communicate and capture prey. This paper reviews some fisheries that have taken advantage of this sensitivity by using sound to help capture numerous species of dolphins and whales. Fishermen in many parts of the world have independently developed methods that use sounds to drive (herd) various species of small cetaceans so that they can be killed and used for food, culled (i.e. to offset competition for fish), help capture fish (e.g. in the Eastern Tropical Pacific) or be taken into captivity. It is well documented that drive fisheries for small cetaceans have occurred for at least 650 years in Japan and Europe. With respect to large whales, the use of sound became widespread after World War II, with the advent of an early form of sonar (ASDIC) which was used for hunting both baleen and sperm whales. Baleen whales displayed a strong avoidance reaction to ASDIC by swimming rapidly away from the sound while remaining near the surface of the water. In contrast, sperm whales made longer dives in response to ASDIC. During the 20th Century, fishermen using these two acoustical methods killed millions of cetaceans (including those caught in the Eastern Tropical Pacific tuna fisheries), both small and large. The effectiveness of acoustic capture methods shows that a wide range of cetacean species have strong avoidance reactions to a variety of anthropogenic sounds. Research to better document the characteristics of these sounds, including those used in existing drive fisheries and those produced by ASDIC devices, would improve understanding of the types of anthropogenic sounds that could contribute to mass-stranding events and should be minimised in protected habitats for cetaceans.